A study on physical access control using QR code as virtual identification system for door access control - Rajangeran, Ashvini Priya; Sandra Sekaran, Puvanah; Sidi, Fatimah; Hairani, Saiful Ramadzan; Daud, Mohd Faizal; Razak, Rizal (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
The increase in criminal activities in today’s world is the cause of tremendous development in safety measures across the nation. One of the widely used safety measures is physical access control. Authentication methods of physical access control such as keys, biometrics (fingerprint, retinal scan), smart cards and One Time Password (OTP) require additional equipment and a high cost to purchase, install and to maintain it, whereby many organizations depending on their specific industry and its requirement along with budget allocation, may choose to opt for these features or not. Unfortunately, tools like keys and smart cards are not unique to specific users and could be possibly misplaced due to human error. OTPs are normally received as text messages on mobile devices and it could be accessed by other parties than the actual individual under minimal supervision by the owner of the device. In this innovative era, smartphones play a noteworthy part in our daily life. This device is easily detectable when it has been misplaced since it is being habitually utilized everyday. Hence, smartphone is utilized in our research due to its deliberate availability. An element that will be corporated on the device, is the Quick Response (QR) code. A QR code can now, not just solely save massive records, but additionally has the error-correction capacity. The QR code has been provided to each UPM students in the PutraVID (Putra Virtual Identification) application as a physical access control tool. The PutraVID has implemented the usage of QR code in the campus for everyday use. Although the QR code is utilized in a huge scale in the campus, there is no particular system to differentiate UPM students and the public, as they not more wearing their matric card or staff ID card as they used to prior to the introduction and implementation PutraVID. The campus environment became vulnerable to attacks as it became an opportunity for unauthorized people to trespass the facilities and caused damages. In order to cope with this issue, QR code is generated in PutraVID which is unique to individuals, as it contains their information such as matric number and name. This information is encrypted into a two-dimensional matrix code, used to scan and access facilities especially restricted areas. The QR code will not be the same for two people, as each student has their individual information stored in it, in order to avoid outsiders from having access to the campus environment. Hence, the entire ecosystem for this system is researched and developed in this paper inclusive of the hardware and software part which proficiently handles the problem. The system develops a centralized door access control management system which is used to store the time stamp of students and staff, and introduces an IoT-based door access control system using the QR code of PutraVID.